2012
DOI: 10.1091/mbc.e11-08-0719
|View full text |Cite
|
Sign up to set email alerts
|

The cytoskeletal mechanisms of cell–cell junction formation in endothelial cells

Abstract: Cell–cell contact is initiated by lamellipodia, followed by filopodia-like structure formation. Filopodia-like bridges maintain cell–cell contact through adherens junctions. Although bridges are structurally similar to filopodia, they are formed via a unique mechanism. Myosin II activity is important for bridge formation and cadherin accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
120
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 60 publications
14
120
0
1
Order By: Relevance
“…In the first step, VE-cadherin engagement is mediated by lamellipodia that subsequently disappear and second remodel into filopodia-like structures as evidenced by the presence of fascin and the vasodilatator-stimulated phosphoprotein (VASP). 46 Vice versa, cadherin induces actin polymerization as shown for E-cadherin in 2002 and has been demonstrated to be required for junction extension while being controlled by the ARP2/3 complex in epithelium. 20 This process was demonstrated to use α-actinin-4 as a bridge molecule between adherens junctions and actin filaments in MDCK cells.…”
Section: Junction Dynamics Is Controlled By Lammellipodia and Filopodiamentioning
confidence: 98%
See 2 more Smart Citations
“…In the first step, VE-cadherin engagement is mediated by lamellipodia that subsequently disappear and second remodel into filopodia-like structures as evidenced by the presence of fascin and the vasodilatator-stimulated phosphoprotein (VASP). 46 Vice versa, cadherin induces actin polymerization as shown for E-cadherin in 2002 and has been demonstrated to be required for junction extension while being controlled by the ARP2/3 complex in epithelium. 20 This process was demonstrated to use α-actinin-4 as a bridge molecule between adherens junctions and actin filaments in MDCK cells.…”
Section: Junction Dynamics Is Controlled By Lammellipodia and Filopodiamentioning
confidence: 98%
“…The circumferential junction-associated actin bundles are characteristic for intact endothelium in vivo, while stress fibers preferentially appear when endothelium becomes activated e.g., under inflammatory conditions and wound healing; conditions that are generally associated with cell proliferation and migration. 1,9,37,44 Actin networks mostly appear, like in other cells, as lammellipodia at the leading edge of migrating cells 11,45,46 and as junctionassociated intermittent lamellipodia (JAIL) at established cell junctions. 11 Those networks are of critical importance in controlling endothelial barrier function and remodeling (for details, see below).…”
Section: Short Overview Of Actin Filaments In Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of time-dependent cytoskeleton changes were confined to specific subcellular space with studies spanning from the peripheral actin-rich lamellipodium for cell-cell connection formation [Jamora and Fuchs, 2002;Mège et al, 2006;Baum and Georgiou, 2011;Hoelzle and Svitkina, 2012] and migration of various cell types [Yamaguchi and Condeelis, 2007;Bergert et al, 2012;Suraneni et al, 2012] to the perinuclear region, and its involvement in intracellular [Campbell and Hope, 2003;Tian et al, 2010] and extracellular signal transduction [Huang et al, 2004;Li et al, 2014]. At the subcellular scale, intensity values, orientation, structural count, density changes, and actin length changes are a subset of the dynamic parameters used to quantify cytoskeleton changes [Muralidhar et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion proteins involved in cell-cell junctional complexes may interact with cytoskeletal and signaling proteins, which allows the anchoring of the adhesion proteins to F-actin and the transfer of intracellular signals inside the cell [7][8][9][10]. It is also known that there are the molecular linkages between cadherins and F-actin in AJs; however, the structural organization and specific role of the actin cytoskeleton at adherens junctions still remains unknown, particularly for endothelial cells [4][5][6]11]. It has also been suggested that the transmigration of monocytes through circular openings is limited by F-actin and partially by alpha-catenin, resulting in monocyte accumulation in atherosclerotic plaques [12][13].…”
Section: Introductionmentioning
confidence: 99%